NK cell signaling to cytotoxicity - parts II & III - Billadeau, Dan (Henry Stewart Talks, 2010)
Regulation of killing by the NKG2D/DAP10 receptor complex, PI3K pathway regulates cell adhesion and MTOC polarization through a CrkL-Rap1 activation, Grb2/Vav1 pathway regulates SLP-76 and PLCγ2 activation, calcium signaling and cell-mediated killing, Inhibitory signaling from killer immunoglobulin receptors that recruit the tyrosine phosphatase SHP1, SHP1 targets